Pregnancy-associated breast cancer: the risky status quo and new concepts of predictive medicine - Polivka, Jiri; Altun, Irem; Golubnitschaja, Olga (The EPMA journal, 2018)
The paper is motivated by severe concerns regarding currently applied care of the pregnancy-associated breast cancer (PABC) characterised by particularly poor outcomes of the disease. Psychological and ethical aspects play a crucial role in PABC: the highest priority not to damage the foetus significantly complicates any treatment generally, and it is quite usual that patients disclaim undergoing any breast cancer treatment during pregnancy. Although, due to global demographic trends, PABC is far from appearing rarely now, severe societal and economic consequences of the disease are still neglected by currently applied reactive medical approach. These actualities require creating new strategies which should be better adapted to the needs of the society at large by advancing the PABC care based on predictive diagnostic approaches specifically in premenopausal women, innovative screening programmes focused on young female populations, targeted prevention in high-risk groups, and optimised treatment concepts. The article summarises the facts and provides recommendations to advance the field-related research and medical services specifically dedicated to the PABC care.
Keywords: Multi-level diagnostics; Breast cancer; Pregnancy; Predictive preventive personalised medicine; Risk assessment; Recommendations